Mesures et assurance qualité dans l'enseignement supérieur au Mexique - Sylvie Didou-Aupetit (Les éditions de la Maison des sciences de l'Homme, 2005)
In Mexico, measurement in itself has not been the subject of reflection. On the other hand, it has been fundamental in the construction of data, which have been produced for 15 years by the various national evaluation and quality assurance bodies. Measurement has also been important in ranking higher education institutions and individuals and in the adoption by the government of new modes of financing public universities. Its uses are thus problematic, in relation to the topics concerned but also for the whole of the system, its organization and its hierarchies as are its links with competitive financing policies. In spite of this, we find a rapid increase in the number of consumers of quality assurance and a tendency, amongst certain sectors of the consumers, to seek out quality labels from international or foreign bodies, be they specialised or not in the field of education. It is thus necessary to critically look at the tensions around the functions of measurement and the success of certain forms and to analyze them in the context of the global reform of higher education, in which traditional relations between the State, higher education institutions and academic actors are profoundly affected to the benefit of the new players.